MONEY LAUNDERING IN THE DIGITAL WORLD: CASE STUDIES (Third Sector Social Economic Review, 2022)
Black money is money that is earned through illegal activity. Since black money is not reported or registered in the financial system of the country where it is found, it damages the country’s economy and leads to measurement error in economic values.  The reason for using the concept of black money is that the income is earned by committing a crime and should be laundered to make it look clean. With rapidly advancing technology in this era and the changing financial regulations with it, many gaps have emerged for money laundering. Considering the accelerating international money transfers and the liberalization of cryptocurrency markets, it has become much easier to attach meaning to money and ensure its circulation.  However, this convenience has led to many money scandals of unknown origin. The facilities provided by the internet today have created an environment that is suitable for abuse and led to the formation of platforms that are difficult to follow. This problem has come to the fore with the increase in money laundering transactions and the mediating role of cryptocurrencies. Some events that emerged in Turkey through social media are cited and explained as examples in this study. This study aims at making contribution to the literature by using the concepts of crime, cryptocurrency, and black money together. The purpose of this study is to determine the deficiencies that are disclosed, and the measures taken by societies and states in today’s conditions.
Keywords: Black Money; Phishing; Cryptocurrency; Crime; Blockchain